2000
DOI: 10.1139/v00-063
|View full text |Cite
|
Sign up to set email alerts
|

Superamidines 2. Synthesis of the bulky ligand N,N'-bis-(2,6-diisopropylphenyl)-trifluoroacetamidine and its molybdenum carbonyl complex

Abstract: N,N'-bis-(2,6-diisopropylphenyl)trifluoroacetamidine has been prepared for the first time from 2,6-diisopropylaniline and the trifluoroacylation reagent TFAP via the imidoylchloride. The crystal structure of the amidine was determined, indicating that it crystallizes in the Z-anti tautomer, in contrast to the nonfluorinated analogue, which is E-anti in the solid state. In solution, as indicated by NMR spectroscopy, it exists in two isomeric forms. The amidine reacts with Mo(CO)6 to produce a coordination compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…Similarly, since our report on the bulky guanidine (E = N,N,N) [10], there have been several other reports on bulky guanidine and guanidinate derivatives. We have demonstrated that the presence of these bulky groups -which are completely unnecessary to stabilize the organonitrogen architectures -induces significant differences in the structure and chemical behaviour of these functional groups in comparison to small organic substituents [6,10].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similarly, since our report on the bulky guanidine (E = N,N,N) [10], there have been several other reports on bulky guanidine and guanidinate derivatives. We have demonstrated that the presence of these bulky groups -which are completely unnecessary to stabilize the organonitrogen architectures -induces significant differences in the structure and chemical behaviour of these functional groups in comparison to small organic substituents [6,10].…”
Section: Introductionsupporting
confidence: 61%
“…Since our initial work on what at the time were the bulkiest amidines to have been reported [6], there has been an explosion of interest in the chemistry of amidines and their deprotonated amidinate congeners [8], coinciding with the fascinating reports from Jordan on alkene polymerization using dimethylaluminium derivatives of amidines which operate without the addition of any transition metals [9]. Similarly, since our report on the bulky guanidine (E = N,N,N) [10], there have been several other reports on bulky guanidine and guanidinate derivatives. We have demonstrated that the presence of these bulky groups -which are completely unnecessary to stabilize the organonitrogen architectures -induces significant differences in the structure and chemical behaviour of these functional groups in comparison to small organic substituents [6,10].…”
Section: Introductionmentioning
confidence: 81%
“…This reaction most often produces amidinate complexes 2,6-8 and much more rarely affords nondeprotonated amidine metal derivatives. 1, [9][10][11][12][13] An other approach to the synthesis of amidine complexes is based on the nucleophilic addition of various NH con taining compounds (for example, of primary or secondary amines, diamines, aziridine, amino alcohols, or amino acid esters 14-17 ) to coordinated nitriles or generation of amidine ligands in the metal mediated transformations involving the above mentioned amino containing nucleo philes in nitrile media. These reactions readily proceed if nitrile substrates are coordinated to metal centers, such as Co III , 18 Cu I , 19 Rh III , 20 W II , 21 Re IV , 22 Ir I , 23 Pt II , or Pt IV .…”
mentioning
confidence: 99%
“…The systematic absences uniquely identified the space group as P2 1 /n (No. 14) in each case and the structures were solved by direct methods with SHELXS and the atomic models refined against F 2 with SHELXL [20]. The "observed data" threshold for calculating the R(F) residuals was set as I > 2(I).…”
Section: Methodsmentioning
confidence: 99%